ANALYSIS OF THE POSSIBILITY OF A STAGED GROWTH OF SPORTS RESULTS OF COUNTRY HIGH JUMPS BY PREPARATORY GROUPS - Tokhtaboev, Nizom (Журнал иностранных языков и лингвистики, 2022)
In this article, an analysis of the possibility of training groups of high-jumper girls' sports results of our country is made, and the analysis of the possibility of step-by-step growth of the sports results of high-jumper girls of our country is widely covered.